THE AMERICAN CONSCIENCE FROM PRAGUE TO HIROSHIMA: PEACE PSYCHOLOGY TOWARD A NUCLEAR-FREE WORLD WITHOUT FIRING A SHOT - Yatani, Choichiro (European Scientific Journal, ESJ, 2015)
The 9/11 and the subsequent Afghanistan and Iraq Wars failed to meet the ardent but sincerest expectations of all the people in the world who longed for the world peace. The 20th century was characterized by the most tragic inhumanity of the never-ending wars: the two world wars and the subsequent Cold War: wars in Korea, Vietnam, central America and elsewhere. It was as if the two superpowers had displaced their conflicts to avoid a nuclear war erasing the human race. The height of the Cold War during the 1980s also brought about the nuclear disarmament movement by people across the globe while one of the two superpowers, an “evil empire” (Reagan,1983), was falling as best symbolized by the fall of Berlin Wall in 1989. During the disappearing of the “enemy” and the building of world peace in the early 21st century, the author argues, the only superpower has come to a standstill in leading the way to defeat the “new enemy” or win the world peace, not due to the lack of its military might, but because of its reckoning filtered through the Cold War, an old mindset proved wrong: “[M]oral leadership is more powerful than any weapon,” according to President Obama’s Prague speech, the Noble Peace Prize recipient in 2009. This research presents such variables as nationalism, nuclear politics, powerlessness and conscience. The author points to America’s declaration in Hiroshima of “no first-use of a nuclear bomb” as the way to world peace in the 21st century.